An emotional security community under pressure? Emotional discursive (de)legitimation in EU external border control. Issue 2 (15th March 2021) - Palm, Trineke
ABSTRACT: This article analyzes How do emotion norms and emotional norms (de)legitimize the EU as a security community? Conceptually, the article expands on the emotional underpinnings of a security community by distinguishing between emotion norms and emotional norms. This then allows to examine emotional (de)legitimation at the level of policy content (i.e. emotional norms) and policy process (i.e. emotion norms). Methodologically, the article develops a framework for an emotion discourse analysis that distinguishes between the valence and social dimension of emotional vocabulary. Empirically, it shows how the discursive (de)legitimation of the EU as a security community in one of the most dynamic fields of EU security policy, external border control, (1) revolves around four emotional norms (effectiveness, responsibility, solidarity and sovereignty) and (2) reflects a struggle about the constitutive emotion norm of a security community: trust.